Strategi Manajemen Untuk Menghadapi Persaingan Bisnis Yang Dinamis: Studi Kasus UMKM Di Surabaya : Management Strategi To Face Dynamic Business Competition: Case Study Of UMKM In Surabaya - Ibrahim Ramadhan (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2025)
This study aims to examine the management strategies implemented by the “Pisang Kribo” UMKM in Surabaya in facing the challenges of the snack industry market. The research approach used is qualitative with a case study method, through in-depth interviews, observation, and documentation. The results of the study indicate that “Pisang Kribo” implements strategies based on SWOT analysis, product innovation, digital marketing, and strengthening partnerships to increase competitiveness. Some of the challenges faced include limited capital, human resources that are not yet digitally ready, and fluctuations in raw material prices. This UMKM overcomes these challenges through collaboration with local cooperatives, digital training, and exploring private investors. The marketing strategy is carried out through a 4P mix which includes product innovation, competitive pricing, multi-channel distribution, and active promotion on social media. This study concludes that the integration of data-based management strategies, technology utilization, and innovative approaches is the main key to the sustainability and growth of UMKM in a dynamic business era.